Kepuasan sebagai mediasi pengaruh motivasi kerja dan iklim kerja terhadap kinerja karyawan - Putra Muhammad Alansyah (MBR (Management and Business Review), 2018)
This research focuses on the employee performance and job satisfaction. This research to analysis the influence of motivation and work climate to job satisfaction, the influence of motivation and work climate on employee performance, the influence of job satisfaction on employee performance, the influence of motivation on employee performance through job satisfaction, work climate on employee performance through job satisfaction. This research was conducted at PT. Hajar Aswad Probolinggo, with a sample 67 employees. The analysis technique used is Path Analysis. The result of the research shows that motivation and work climate have a significant effect on job satisfaction, motivation and work climate have a significant effect on employee performance, job satisfaction has a significant effect to employee performance, motivation has a significant effect on employee performance and job satisfaction, work climate has a significant effect on employee performance and job satisfaction, job satisfaction effectively mediates motivation and work climate on performance.